2014
DOI: 10.1364/oe.22.004896
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-distributed Ultra-wideband noise radar with steerable power spectrum and colorless base station

Abstract: A fiber-distributed Ultra-wideband (UWB) noise radar was achieved, which consists of a chaotic UWB noise source based on optoelectronic oscillator (OEO), a fiber-distributed transmission link, a colorless base station (BS), and a cross-correlation processing module. Due to a polarization modulation based microwave photonic filter and an electrical UWB pass-band filter embedded in the feedback loop of the OEO, the power spectrum of chaotic UWB signal could be shaped and notch-filtered to avoid the spectrum-over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The authors demonstrated ranging measurements with 10-cm and 20-cm resolution after 10-km fiber transmission. In [32], Zheng et al proposed and demonstrated a novel fiber-distributed chaotic UWB noise radar, which consists of a chaotic UWB noise source based on optoelectronic oscillator, a fiberdistributed transmission link, a colorless base station, and a cross-correlation processing module. Especially, the power spectrum of chaotic UWB signal could be shaped and notchfiltered to avoid the spectrum-overlay-induced interference to the narrow band signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated ranging measurements with 10-cm and 20-cm resolution after 10-km fiber transmission. In [32], Zheng et al proposed and demonstrated a novel fiber-distributed chaotic UWB noise radar, which consists of a chaotic UWB noise source based on optoelectronic oscillator, a fiberdistributed transmission link, a colorless base station, and a cross-correlation processing module. Especially, the power spectrum of chaotic UWB signal could be shaped and notchfiltered to avoid the spectrum-overlay-induced interference to the narrow band signals.…”
Section: Discussionmentioning
confidence: 99%
“…In our preliminary experiments, we proposed a UWB microwave-photonic chaotic radar for remote ranging [30] and for remote water-level monitoring [31]. In 2014, Zheng et al demonstrated a fiber-distributed UWB noise radar, which has a space resolution with cm-level after 3-km fiber transmission [32]. In this paper, we demonstrate a microwave-photonic chaotic UWB radar system for remote ranging based on the chaotic signal generation and fiber-optic distribution, which has potential for military radar, hilltop under the bad conditions, the radar systems in islands, dangerous areas and harsh industrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Using fiber optic links for radar signal distribution has been investigated in previous studies. In [5] and [6], an ultra-wideband (UWB) radar signal was generated and converted into an optical signal using a polarization modulator. The optical signal was then transmitted over a 3-km singlemode fiber (SMF).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we propose a cost-effective all-optical transport network for radar signal distribution. Instead of dedicating one complete radar system for each site as proposed in previous studies [3]- [6], [9], we consider generating one radar signal in the central office (CO) and then transmitting it over one selectable branch of a point-to-multipoint optical network by exploiting the SOA's wavelength conversion function in the CO as discussed in Section 2. Because of the limitation of hardware availability in our lab, the demonstration and analysis are performed over the downstream link for signal distribution only (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clock synchronization between the sensor nodes is complicated and has limited accuracy, which degrades again the localization accuracy [6,10]. Photonic approaches to realize position localization can achieve high-resolution and provide the possibility to move the signal processing from sensor nodes to the central station, thanks to the low loss, immunity to EMI and broad bandwidth brought by the photonic technologies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%